Highly sensitive spectrophotometric methods for the determination, validation and thermogravimetric analysis of antiulcer drugs, nizatidine and ranitidine in pure and pharmaceutical preparations - Ulu, Sevgi Tatar; Elmali, Fikriye Tuncel (PLEIADES PUBLISHING INC, 2013)
Two sensitive, simple and rapid UV and second order derivative spectrophotometric methods were developed for the determination of nizatidine and ranitidine hydrochloride in pure form and pharmaceutical preparations. For the first method, UV spectrophotometic method, nizatidine was determined at 325 nm and ranitidine at 325.5 nm with detection limits of 0.07 and 0.04 mu g/mL, respectively. For the second method, the distances between two extremum values (peak-to-peak amplitudes), 328/356.5 nm for nizatidine and 326/357 nm for ranitidine were measured in the second order derivative-spectra. The detection limits were found to be 0.02 mu g/mL for nizatidine and 0.016 mu g/mL for ranitidine, respectively. The thermal analysis of the two drugs was studied by Thermogravimetric Analysis-Differential Scanning Calorimetry (TGA-DSC) techniques. Enthalpy changes were obtained 121.9 and 124.15 J/g for nizatidine and ranitidine, respectively. The proposed method was successfully applied to the analysis of pharmaceutical preparations. The results were in good agreement with those obtained using the reference method; no significant difference were found in the accuracy and precision as revealed by the accepted values of t- and F-tests.
Keywords: UV derivative spectrophotometry; thermogravimetric analysis-differential scanning calorimetry; ranitidine; nizatidine; LIQUID-CHROMATOGRAPHIC METHOD; HUMAN PLASMA; HPLC METHOD; METABOLITES; FAMOTIDINE; CIMETIDINE; URINE; Chemistry